Online collective efficacy and its relationship with organizational sustainable development in higher education - Ashraf Ragab Ibrahim; Ibrahim Mohammed Ibrahim; Billal Mohamed Aboelhasayb; Mohammed Maher Mohammed; Ahmed Metwally Eissa; Mohamed Ali Nemt-allah (International Journal of Evaluation and Research in Education (IJERE), 2026)
Digital transformation in higher education has intensified reliance on online collaboration, yet the role of shared digital capability beliefs in driving institutional sustainability remains underexplored. This study examined the relationship between online collective efficacy (OCE) and organizational sustainable development (OSD) among faculty members in Egyptian higher education. Using a quantitative correlational design, a purposive sample of 647 faculty members and teaching assistants from Al-Azhar University completed two validated instruments: the OCE scale and the OSD questionnaire. Pearson correlation and multiple regression analyses revealed exceptionally strong positive associations between all OCE dimensions and OSD outcomes (r=.887, p